2017
DOI: 10.1016/j.yjmcc.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altered haemodynamics on the developing mitral valve in chick embryonic heart

Abstract: Intracardiac haemodynamics is crucial for normal cardiogenesis, with recent evidence showing valvulogenesis is haemodynamically dependent and inextricably linked with shear stress. Although valve anomalies have been associated with genetic mutations, often the cause is unknown. However, altered haemodynamics have been suggested as a pathogenic contributor to bicuspid aortic valve disease. Conversely, how abnormal haemodynamics impacts mitral valve development is still poorly understood. In order to analyse alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 88 publications
1
22
0
Order By: Relevance
“…These features are in line with previously reported characteristics of pressure overloaded embryonic hearts (Sedmera et al ; Tobita et al ; Hall et al ). Consistent with the literature (Pang et al ), phenotypic analysis revealed a VSD at HH29 (n = 26/31) (Fig. Bb,b’; denoted by an asterisk in Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These features are in line with previously reported characteristics of pressure overloaded embryonic hearts (Sedmera et al ; Tobita et al ; Hall et al ). Consistent with the literature (Pang et al ), phenotypic analysis revealed a VSD at HH29 (n = 26/31) (Fig. Bb,b’; denoted by an asterisk in Fig.…”
Section: Resultssupporting
confidence: 91%
“…In addition, previous data from our group show changes in the ECM of the epicardium at a molecular and morphological level with a progressive aberrant phenotype from HH29 to HH35 (Perdios et al ). However, overall embryonic growth was not affected upon banding, as the cardiac output and overall embryo size are the similar in control and banded embryos (Clark et al ; Keller et al ; Pang et al ). In this study, evidence is provided of molecular mechanisms involved in OFT‐banded hearts, highlighting potential cardioprotective responses, with further analyses characterising the levels of apoptosis and glycogen accumulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Heterospecific interactions between a small number of the transcription factors Tbx5 and Nkx2.5, and GATA4, also part of the cardiogenic tool kit, underlying gene expression patterns in specific tissues, have been demonstrated in mammalian cardiogenesis . However, this shows much complexity and requires fine‐tuning involving additional partners, including histone modifications, epigenetic regulation, involvement of hemodynamics, regulation of cell movement, and participation of microRNAs to provide for expansion of cardiac progenitors, compartments, and cell differentiation.…”
Section: The Second Heart Fieldmentioning
confidence: 99%
“…Gene regulatory networks in the cardiac tool kits have been studied in mammalian embryos. These include but are not limited to Notch1, Slit‐Robo, Krox 20, Wnt signaling, TGFβ signaling, NFATc1, ADAM17, Msx, and matrix proteins such as laminin, versican, periostin, hyaluronan, tenascin and fibrillin, elastin, collagens, and others (see Pucéat).…”
Section: The Oft Endocardial Cushionsmentioning
confidence: 99%